2023
DOI: 10.3389/fbioe.2023.1040762
|View full text |Cite
|
Sign up to set email alerts
|

The roles and therapeutic potentialof mesenchymal stem/stromal cells and their extracellular vesicles in tendinopathies

Abstract: Tendinopathies encompass a highly prevalent, multi-faceted spectrum of disorders, characterized by activity-related pain, compromised function, and propensity for an extended absence from sport and the workplace. The pathophysiology of tendinopathy continues to evolve. For decades, it has been related primarily to repetitive overload trauma but more recently, the onset of tendinopathy has been attributed to the tissue’s failed attempt to heal after subclinical inflammatory and immune challenges (failed healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 114 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…This condition also involves the dysregulated recruitment of immune cells and inflammatory mediators, eventually leading to increased cellular apoptosis ( Figure A). [ 4a,65 ] The adult tendon contains densely packed collagen fibrils responsible for transmitting force from muscle to bone. [ 66 ] Tendinopathy occurs due to tendon rupture and repetitive mechanical loading, forming scars as tendons fail to heal completely or regain their mechanical function.…”
Section: Tendinopathymentioning
confidence: 99%
“…This condition also involves the dysregulated recruitment of immune cells and inflammatory mediators, eventually leading to increased cellular apoptosis ( Figure A). [ 4a,65 ] The adult tendon contains densely packed collagen fibrils responsible for transmitting force from muscle to bone. [ 66 ] Tendinopathy occurs due to tendon rupture and repetitive mechanical loading, forming scars as tendons fail to heal completely or regain their mechanical function.…”
Section: Tendinopathymentioning
confidence: 99%
“…Tendon stem/progenitor cells (TSPCs) are self-renewing pluripotent cells present in tendons and are an important cell source for tendon tissue repair and regeneration [ 13 , 14 ]. TSPCs exhibit can not only differentiate into various cell types, including bone cells, chondrocytes, and adipocytes, but also regulate immune responses and play an important role in maintaining the physiological functions of tendons, including elasticity, flexibility, and tensile strength [ 15 , 16 ]. Rui et al [ 17 ] and Zhang et al [ 18 ] successfully isolated and cultured TSPCs in the tendon tissues of rats and rabbits, respectively, and found that these cells could differentiate toward tendon formation under certain conditions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%